A multi-objective optimization of FCL and DOCR settings to mitigate distributed generations impacts on distribution networks. (May 2023) - Usama, Muhammad; Mokhlis, Hazlie; Nadzirah Mansor, Nurulafiqah; Moghavvemi, Mahmoud; Naveed Akhtar, Muhammad; Akram Bajwa, Abdullah; Jamilatul Awalin, Lilik
Highlights: A combined protection strategy to incorporate the FCL deployment and DOCR settings to alleviate the miscoordination at high faulted nodes irrespective of DG location and network operating state. Monte Carlo Simulation (MCS) is implemented to predict the locations where the fault currents exceed the CB thermal limits due to essential network growth. The relay settings are optimized as one setting group to maintain the coordination in the network dynamic operating state, i.e., Grid (On/Off). The multi-objective hybrid optimization technique is formulated to minimize the FCL implementation cost and DOCR coordination settings by considering user-defined characteristics. The proposed hybrid LP is considered with the SSA algorithm to solve PCP by linearizing the relay characteristics equation. Abstract: Despite providing increased reliability and power quality in meeting the load demand, the integration of DGs has imposed challenges on the protection system. High penetration of DGs changes the overall network impedance and increases the fault current level in the network. Consequently, some buses are exposed to critical conditions, violate the circuit breakers (CB) handling capacity, and affect the existing relay coordination settings. To mitigate these adverse impacts, fault current limiters (FCL) can be a potential solution to minimize the short circuit current within permissible switchgear-rated limits. Due to its expensive cost, it is crucial to ensure the optimal FCL placement and sizing, and at the same time maintain the effectiveness of the protection performance during various network operation states. This research formulates FCL and directional overcurrent relay (DOCR) settings as a combined protection coordination scheme optimized by a multi-objective hybrid optimization technique. The proposed formulation aims to determine the minimal FCL sizing with minimum investment cost to satisfy the relay coordination constraints at high fault-level buses, irrespective of DG locations and network operating state. User-defined relay characteristics (UDC) are employed to intensify the DOCR coordination performance and obtain minimum operating time, where the conventional inverse relay constants (A&B) are optimized with (TSM & Ipu). The combined UDC relay settings and FCL problem formulation solution attained by MO-hybrid optimization can lessen the escalated electromagnetic stresses, costly switchgear replacement, and relay maloperation. The performance of the proposed technique is assessed by implementing it on the radial (IEEE-33 Bus) and meshed (IEEE 30-Bus) DNs with optimized FCL sizing and relay settings. The optimal results demonstrate the effectiveness of the proposed technique in maintaining the relay coordination performance in the presence of DGs and FCL under an ON/OFF grid connection.